Magnetic resonance imaging versus lymphoscintigraphy for the assessment of focal lymphatic transport disorders of the lower limb - Weiss, M.; Burgard, C.; Baumeister, R.; Strobl, F.; Rominger, A.; Bartenstein, P.; Wallmichrath, J.; Frick, A.; Notohamiprodjo, M. (Nuklearmedizin - NuclearMedicine, 2014)
Purpose: To compare the diagnostic accuracy of magnetic resonance imaging (MR-lym- phangiography) and lymphoscintigraphy for assessment of focal lesions of the peripheral lymphatic system. Patients with focal lymphatic transport disorders might benefit from surgi-cal interventions. Patients, methods: We examined by lymphoscintigraphy and MR- lymphangiography a total of 85 lower limbs in 46 consecutive patients (33 women; mean age 41 years; range 9-79 years) presenting with uni- or bilateral lymphedema. MR-lym- phangiographies were obtained at isotropic sub-millimeter resolution with a 3.0 Tesla magnet after injection of gadolinium contrast medium. MR-lymphangiography was reviewed by radiologists, whereas lymp- hoscintigraphy was reviewed by nuclear medicine physicians. The images were examined for localization and distribution of any focal lesions of the lymphatic vessel system. Diagnostic accuracy of the MR-approach was calculated relative to the lymphoscintigraphy gold standard. Results: There was substantial correlation of results by the two modalities (κ = 0.62). MR-lymphangiography had sensitivity of 68%, specificity of 91%, positive predictive value of 82%, and negative predictive value of 83%. Conclusions: Imaging findings of both lymphoscintigraphy and MR-lymph- angiography showed good diagnostic accuracy. MR-lymphangiography proved more information about anatomic location of focal lesions of the lymphatic vessels, but use of MR-lymphangiography is currently constrained due to the requirement for off-label subcutaneous injection of gadolinium che- lates. Consequently, and due to its superior sensitivity lymphoscintigraphy remains the most common imaging method to assess functional lymphatic disorders of the lower limb.
Keywords: Lymphoscintigraphy; MR-lymphangiography; magnet resonance imaging; lymphoedema; lymphatic disorders